PENGARUH NILAI YANG DIRASAKAN, HARAPAN PELANGGAN, CITRA PERUSAHAAN DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN (STUDI PADA PENGGUNA INDOSAT OOREDOO DI BANDA ACEH) - Maulizar Fahmi; Saed Armia (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2017)
This study aims to determine the effect of perceived value, customer expectation, corporate image and service quality on customer satisfaction. The empirical study conducted at Indosat Ooredoo user in Banda Aceh used a questionnaire as a research instrument, which samples in this study of 150 people they are Indosat Ooredoo’s customers, who have subscribed at least one month. Non-probability sampling is used as a sampling technique with Purposive Sampling. Methods MRA (Multivariate Regression Analysis) is used as a method of data analysis using software IBM SPSS 20. These results indicate that the perceived value is positive and significant related to customer satisfaction, customer expectation is positive and significant related to customer satisfaction, corporate image is positive and significant related to customer satisfaction and service quality is positive and significant related to customer satisfaction, then simultaneoustly perceived value, customer expectation, corporate image and service quality has positive effect on customer satisfaction.Keywords : Perceived Value, Customer Expectation, Corporate Image, Service Quality, Customer Satisfaction.